Building sustainable tourism appeal - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
In conclusion, the programme successfully empowered the Tulungrejo community to organize innovative, sustainable events, strengthening their tourism potential. It highlighted the importance of balancing economic growth with environmental and cultural preservation. Tulungrejo Village has the potential to become a future example of sustainable tourist development with sustained cooperation and community engagement.